2020
DOI: 10.13080/z-a.2020.107.035
|View full text |Cite
|
Sign up to set email alerts
|

Breeding progress in grain filling and grain yield components of six-rowed winter barley

Abstract: The objectives of this study were to quantify the grain yield breeding progress and identify the changes in numerical yield components and grain filling traits of six-rowed winter barley (Hordeum vulgare L.) cultivars under different nitrogen (N) fertilization treatments: 0 kg ha-1 N (0N, control) and 100 kg ha-1 N (100N). Field trials were conducted during two (2015-2016 and 2016-2017) growing seasons in a southern Pannonian location, Novi Sad, Serbia with fifteen six-rowed winter barley cultivars. The rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…The highest variation was observed in Anka-08 (215 spikes) and the lowest variation in SSM was 6 spikes form Calabey (Table 7). Mirosavljević et al (2020) found a significant effect of G, Y, and G x Y interaction. The highest value they obtained range from 406-442.…”
Section: Number Of Spike Per Square Meter (Ssm)mentioning
confidence: 88%
See 1 more Smart Citation
“…The highest variation was observed in Anka-08 (215 spikes) and the lowest variation in SSM was 6 spikes form Calabey (Table 7). Mirosavljević et al (2020) found a significant effect of G, Y, and G x Y interaction. The highest value they obtained range from 406-442.…”
Section: Number Of Spike Per Square Meter (Ssm)mentioning
confidence: 88%
“…The yearly variation was 1.88 seeds, the genotypes Avci 2002, Aydanhanim, Calabey, and Larende were the most affected (4 seeds), whereas Anka-09 and Burakbey showed no variation (Table 7). Mirosavljević et al (2020) found a significant effect genotypes on SPS, with a range value of 48.3-53.1 to 49.8-54.5. However, their research indicated a significant effect of year and G x Y interaction on SPS.…”
Section: Number Of Seed Per Spike (Sps)mentioning
confidence: 91%
“…Odsustvo pozitivne veze između mase 1000 zrna i godine priznavanja, i značajna veza broja zrna po jedinici površine sa godinom priznavanja, jasno ukazuju da se porast prinosa novih sorti bazirao na povećanoj produkciji broja zrna . Prethodne studije na ječmu (Mirosavljević et al ., 2020) i na pšenici (Zhou et al ., 2014) su potvrdile da je broj zrna osnovna komponenta prinosa strnih žita i da se selekcija ovih biljnih vrsta uglavnom bazirala na povećanju ove komponente .…”
Section: Rezultati I Diskusijaunclassified